2018
DOI: 10.1007/s11571-018-9495-z
|View full text |Cite
|
Sign up to set email alerts
|

Graph analysis of functional brain network topology using minimum spanning tree in driver drowsiness

Abstract: A large number of traffic accidents due to driver drowsiness have been under more attention of many countries. The organization of the functional brain network is associated with drowsiness, but little is known about the brain network topology that is modulated by drowsiness. To clarify this problem, in this study, we introduce a novel approach to detect driver drowsiness. Electroencephalogram (EEG) signals have been measured during a simulated driving task, in which participants are recruited to undergo both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…These changes in EEG can be used to detect mental fatigue [10,15], which is especially important and meaningful for driving fatigue estimation [7,11]. From the above, we can conclude that EEG has become the most effective technical means for exploring the neuromechanism and detection of mental fatigue [18,19].…”
Section: Introductionmentioning
confidence: 88%
“…These changes in EEG can be used to detect mental fatigue [10,15], which is especially important and meaningful for driving fatigue estimation [7,11]. From the above, we can conclude that EEG has become the most effective technical means for exploring the neuromechanism and detection of mental fatigue [18,19].…”
Section: Introductionmentioning
confidence: 88%
“…The results suggested that their methodology can achieve an average classification accuracy of 69.5%, and a maximum accuracy of 83.5%. Chen et al, 2018 [132] proposed a novel brainnetworks-based approach to detect drowsiness. EEG signals from 15 male subjects were acquired in a simulated driving task.…”
Section: Electroencephalograph (Eeg)-based Findingsmentioning
confidence: 99%
“…Unfortunately, EEG recordings are generated from the cortex and collected from the scalp. In EEG measurements there always appear complex and non-linear characteristics [6][7][8][9][10]. Understanding the non-linear and complex dynamics underlying EEG measurements is a significant and challenging problem [11].…”
Section: Introductionmentioning
confidence: 99%